Family planning saves lives - Smith, Rhonda...[et al.] (Population Reference Bureau WashingtonUS, 2009)
Provides information on the health benefits of family planning. Provides also, data from the latest research in maternal and child health in developing countries. Includes new information on how family planning reduces the rate of new HIV infections and deaths from AIDS.